FOSTERING DELIBERATIVE GOVERNANCE IN LABOUR SOCIAL INSURANCE POLICY INNOVATION: THE CASE OF CENTRAL JAVA REGIONAL GOVERNMENT - Tasroh Tasroh; Paulus Israwan Setyoko; Maharani Anjasmoro Hariga (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Conflicts between labour and regional government continue to occur everywhere. One of the impacts is the problem of the achievement of Employment Social Security participation in Indonesia which is still very low. Data actually stated on November 2024 has only reached 30% of the government's target in 2024 which should have reached 60%. This study aims to explain how deliberation forums (deliberative) in Central Java significantly takes a strategic role in fostering public networking in decison making of labour insurance. By using descriptive-qualitative methods through studies of related policy documents and in-depth interviews with key officials in related agencies, it can be concluded that there are 2 models of deliberative governance in the formulation of labour protection policies that can be developed as an alternative to overcoming the problem of labour protection policy formulation, especially at the local government level. The first is the Elite model, namely policy deliberations managed through collaboration between actors from the government, especially between the executive, legislative and actors from the elements of the Employment Social Security organizers. Second, the “private” model of policy deliberation is a deliberation held collaboratively between actors from the labourur element and the social organization element. The “private” policy deliberation is much more democratic and autonomous, because each actor is free to build interaction patterns and communication flows that are increasingly productive. In brief, through the development of such a deliberative policy model, it has also proven to be a significant innovation in labour protection policies while being able to prevent destructive conflicts and disputes between workers and government in fighting for better labourur social insurance for a safer and more prosperous future for workers as a whole.